The Impact of Interactive Learning Methods on Student Motivation and Achievement in Elementary Schools - Pramesworo, Ignatius Septo; Wajnah, Wajnah; Malik, Abdul; Lamatokan, Sisca Cletus; Nugroho, Agung Yuliyanto (Universitas Tanjungpura, 2025)
This qualitative study explores the impact of interactive learning methods on student motivation and achievement in elementary schools. Through observations, interviews, and document analysis, the research investigates how interactive strategies such as collaborative projects, gamification, and technology-enhanced activities influence students' engagement and academic outcomes. The findings reveal that interactive learning fosters a more engaging and stimulating educational environment, leading to increased student motivation and improved academic performance. The study highlights the importance of incorporating interactive methods into elementary school curricula to enhance the overall learning experience and promote student success.